Tricuspid Annulus Dilation in Patients With Combined Functional Tricuspid Regurgitation and Left-Heart Valvular Disease: Does Septal Annulus Not Dilate? - Teng, Peng; Dai, Xiaoyi; Zou, Yu; Yuan, Shuai; Chen, Yan; Ma, Liang; Ni, Yiming (Frontiers in Cardiovascular Medicine, 2022)
Background This study aimed to investigate the course of tricuspid annulus dilation in functional tricuspid regurgitation with varied severities by direct intraoperative assessment. Methods A total of 317 patients who underwent left heart surgery and concomitant tricuspid repair were divided into three groups according to the severity of the functional tricuspid regurgitation (mild, moderate and severe). Demographic and echocardiographic data were collected. The length of each tricuspid annulus segment was measured intraoperatively. The risk factors for preoperative severe functional tricuspid regurgitation and its postoperative recurrence were identified, and the impact of each tricuspid annulus segment on postoperative recurrence was compared. Results In the course of tricuspid annulus dilation, the posterior annulus dilated 17% (group 1: 33.31 ± 6.94 mm vs. group 2: 35.56 ± 7.63 vs. group 3: 38.98 ± 8.70, p < 0.01), the anterior annulus dilated 13.4% (group 1: 36.71 ± 6.30 mm vs. group 2: 38.21 ± 8.35 vs. group 3: 41.63 ± 9.20, p < 0.01), and the septal annulus dilated 11.4% (group 1: 38.11 ± 5.28 mm vs. group 2: 39.76 ± 6.90 vs. group 3: 42.46 ± 7.50, p < 0.01). Tricuspid annulus circumference index (p < 0.01) independently correlated with preoperative severe tricuspid regurgitation and postoperative recurrence. When patients were grouped based on the length of each segment, the septal annulus demonstrated significantly higher sensitivity (p < 0.001) to postoperative recurrence than the anterior (p = 0.085) or posterior annulus (p = 0.262). Conclusions This study revealed that each segment of tricuspid annulus could dilate in functional tricuspid regurgitation and highlighted the potential benefits of septal annulus plication in tricuspid annuloplasty, which may aid in the development of a methodology for prosthetic ring annuloplasty.